PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PDRB), JUMLAH PENDUDUK DAN PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH (PAD) - Afifah Ariyani; Fitri Yetti; Noegrahini Lastiningsih (Jurnal Ilmiah Wahana Akuntansi, 2018)
This research was conducted to examine the influence of Gross Regional Domestic Product, Population, and Hotel Tax on Local Revenue. Sample of this research uses Regency and City in Java Province from 2014 until 2016. Sampling technique using purposive sampling (purposive sampling method). There is 100 sample of Regency and City in Java Province, resulted in 98 Regency and City that are acceptable. Testing the hypothesis in this study using Multiple Linear Regression Analysis with SPSS 23 and a significance level of 5%. The result of partial test showed that: (1) Gross Domestic Regional Product has a significant positive influence on Local Revenue with a significance level of 0,000. (2) Population has a significant positive influence on Local Revenue with a significance level of 0,000. (3) Hotel Tax has a significant positive influence on Local Revenue with a significance level of 0,000. Keywords : Local Revenue, Gross Regional Domestic Product, Population, Hotel Tax